(untitled) (Physical Education, Health and Social Sciences, 2025)
This study seeks to outline a new vision for Islamic finance that focuses on purpose and Maqāṣid al-Sharīʿah, instead of merely compliance. While contemporary Environmental, Social, and Governance (ESG) frameworks are influential, they are hyper secular and mostly do not capture the ethical and legal dimensions of Maqāṣid. The study addresses Maqāṣid-Driven ESG Framework, a fully normative model which incorporates the theological, operational, and institutional dimensions of finance to an action plan. This concept is framed in three layers all are interrelated dimensions and intentionally designed to guarantee transactions and every investment while securing the spirit of preservation of faith, life, intellect, progeny, and wealth. Incorporating fiqh al-awlawiyyāt reframes ESG from a matter of compliance or voluntary adoption into a requirement grounded in religious duty. The cases of Malaysia, the UAE, and Saudi Arabia show that Islamic ethical principles can be meaningfully integrated into sustainable finance, though several practical obstacles remain among them differing juristic interpretations, resistance masked as compliance, and ongoing difficulties in evaluating ethical performance. The study’s exploration of Maqāṣid-oriented ESG indicators and the use of data-supported ijtihād for measuring impact adds important depth to this discussion. It also introduces the idea of fiqh al-istidāmah, a jurisprudence of sustainability. For Muslim jurisdictions, approaching finance through the lens of Maqāṣid is not simply a policy choice but a Sharʿī duty. Viewed this way, Islamic finance becomes a vehicle for responsible governance, social welfare, and long-term sustainable development.